Drāhyāyana-śrauta-sūtra - Drāhyāyaṇa; Dhanvin; Raghu Vīra (Mehar Chand Lachhman Das, 1940)
Aphoristic work, with commentary, on Hindu sacrificial rites, according to the Drāhyāyana school in Sāmaveda.